Quantitative assessment of sensorimotor dysfunction and recovery using robotics in athletes sustaining an acute sport-related concussion. Issue 5 (11th March 2013) - Benson, Brian; Semrau, Jennifer; Debert, Chantel; Scott, Stephen; Meeuwisse, Willem; Dukelow, Sean
Abstract : Objective: To determine the utility of a novel robotic assessment tool to aid with acute sport concussion assessment and management. Design: Prospective case series. Setting: 2011–2012 athletic season. Subjects: 313 male and female elite athletes (mean age: 21 years). Outcome Measures: Baseline and post-concussion (physician diagnosed) robotic assessments of neurological function using the KINARM end-point robotic device in five different tasks. Results: Twenty-nine of the 313 athletes (9.3%) completing a baseline clinical and robotic assessment in 2011 sustained an acute sport concussion during the 2011–2012 season. Many of the concussed athletes declined in performance on the post-concussion robotic testing (<72 h post-injury). Twenty-two concussed athletes demonstrated increases in the contraction parameter of the multi-target position sense task (p=0.005). Nineteen demonstrated slowing of their movement speed in a bimanual interactive task requiring subjects to hit and avoid various virtual shapes (left hand p=0.03; right hand p=0.09). Twenty-two of the concussed athletes demonstrated increased dwell time/movement time when performing an automated version of the Trails B test (p=0.002). In general, performance trended back towards baseline in the weeks following the concussion. Conclusions: The clinical use of robotics in post-concussion assessment shows promise in objectively quantifying degradation of sensorimotor performance that is not always evident in existing clinical tools. Further analyses is warranted including the development of baseline sensorimotor normative data for high risk athletic populations (with reliable change indexes) and comparing the sensitivity of this device with other standardised measures of clinical concussion recovery (ie, symptoms, neurological examination, balance, and neurocognitive). Acknowledgments: University of Calgary Sport Medicine Centre BKIN Technologies, Queen's University Own the Podium, Canada Jim Smith, Calgary, Alberta Canadian Sport Centre Calgary University of Calgary, Edge High School, and SAIT Athletic Therapists, Physiotherapists, and Coaches Hotchkiss Brain Institute Sarah Snow & Kerri Downer.